High incidence of BSCL2 intragenic recombinational mutation in Peruvian type 2 Berardinelli–Seip syndrome. Issue 2 (21st November 2016) - Purizaca‐Rosillo, Nelson; Mori, Takayasu; Benites‐Cóndor, Yamali; Hisama, Fuki M.; Martin, George M.; Oshima, Junko
Abstract : Congenital generalized lipodystrophy (CGL) is a genetically heterogeneous group of disorders characterized by the absence of functional adipose tissue. We identified two pedigrees with CGL in the community of the Mestizo tribe in the northern region of Peru. Five cases, ranging from 15 months to 7 years of age, presented with generalized lipodystrophy, muscular prominence, mild intellectual disability, and a striking aged appearance. Sequencing of the BSCL2 gene, known to be mutated in type 2 CGL (CGL2; Berardinelli–Seip syndrome), revealed a homozygous deletion of exon 3 in all five patients examined, suggesting the presence of a founder mutation. This intragenic deletion appeared to be mediated by recombination between Alu sequences in introns 2 and 3. CGL2 in this population is likely underdiagnosed and undertreated because of its geographical, socio‐economic, and cultural isolation.© 2016 Wiley Periodicals, Inc.